Cataract and quality of life in patients with glaucoma. (30th October 2014) - Skalicky, Simon E; Martin, Keith R; Fenwick, Eva; Crowston, Jonathan G; Goldberg, Ivan; McCluskey, Peter
Abstract Background To assess the impact of cataract on quality of life (QoL) for patients with glaucoma. Design Cross‐sectional study. Participants Two hundred forty‐two patients with mild (n = 67), moderate (n = 80) or severe (n = 45) glaucoma and 50 controls (glaucoma suspects). Patients with cataract of any severity were included. Methods The following data were collected: sociodemographic information, phakic/pseudophakic status, cataract grade according to the Lens Opacities Classification System (LOCS) III, visual acuity and visual field test parameters. Glaucoma severity was stratified according to binocular visual field loss. Visually significant cataract was defined as: LOCS III criteria nuclear cataract ≥3/6.9, cortical cataract ≥3/5.9 or posterior subcapsular cataract ≥2/5.9. Main Outcome Measures Patients' QoL was measured using Rasch‐transformed scores from the Glaucoma Activity Limitation‐9 (GAL‐9) questionnaire. Multiple linear regression models were used to determine the association between cataract and GAL‐9 (logit) score. Results Fifty‐six (23.1%) patients had at least one visually significant cataract. At least one visually significant cataract (standardized coefficient [β] 1.19, 95% confidence interval 1.04–1.34, P = 0.011) and poor visual field index (better eye) (β 1.47, 95% confidence interval 1.36–1.88, P < 0.001) were independently associated with worse GAL‐9 score. Conclusions Cataract influences glaucoma‐related QoL among glaucoma patients of all severity levels and is an important cause of potentially reversible visual impairment among glaucoma patients. The Rasch‐analysed GAL‐9 questionnaire is a useful metric to quantify visual disability related to cataract in glaucoma patients.